Evaluation of teaching modalities adopted by trainers to educate special children - S Rajakumar; M Jayanthi; Elizabeth Joseph (SRM Journal of Research in Dental Sciences, 2012)
Aim and objectives: oral health is an important aspect of general health in special children and impacts the quality of life and health outcomes. The role of the special educators has become more imperative in promoting oral health care in special children. The aim of this study was to evaluate the teaching modalities adopted by trainers to educate special children. Materials and methods: An interview was conducted to 40 special trainers with a set of structured questionnaires to gain information about the methods adopted by them to train special children and also to find out their level of awareness about the importance of maintaining good oral health and dental treatment. Results and conclusion: The knowledge and awareness about oral hygiene that is to be instructed for special children is well known by the trainers and almost 80% of the trainers implement it in their daily practice. They use different techniques in training the special children and group them according to their condition and train as per their requirements. Dentists can adopt trainers methodology of teaching special children during critical times.